Root, Tuber and Banana Food System Innovations 2022
DOI: 10.1007/978-3-030-92022-7_12
|View full text |Cite
|
Sign up to set email alerts
|

Securing Sweetpotato Planting Material for Farmers in Dryland Africa: Gender-Responsive Communication Approaches to Scale Triple S

Abstract: Triple S (Storage in Sand and Sprouting) is a root-based system for conserving and multiplying sweetpotato planting material at the household level. In sub-Saharan Africa, farmers predominantly source planting material by cutting vines from volunteer plants that sprout from roots left in the field from a previous crop. However, it takes 6 to 8 weeks after the rains start to produce enough vines for planting material, and normally these vines are infected by sweetpotato diseases and pests carried over from prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Men in the same village mentioned that some neighbours give vines for free, while others sell them. In Agirinyi village for example, 6 farmers (3 M, 3F) indicated that they have bought vines from their neighbours in the past, which corroborates the findings by McEwan et al (2022) and Rachkara et al (2017) with regards to the commercial perspective of vine sourcing in arid and semi-arid regions when compared to those with bimodal rainfall patterns.…”
Section: Constraints To Adoption Of Existing Improved and Local Sweet...supporting
confidence: 75%
See 1 more Smart Citation
“…Men in the same village mentioned that some neighbours give vines for free, while others sell them. In Agirinyi village for example, 6 farmers (3 M, 3F) indicated that they have bought vines from their neighbours in the past, which corroborates the findings by McEwan et al (2022) and Rachkara et al (2017) with regards to the commercial perspective of vine sourcing in arid and semi-arid regions when compared to those with bimodal rainfall patterns.…”
Section: Constraints To Adoption Of Existing Improved and Local Sweet...supporting
confidence: 75%
“…For instance, improved varieties such as NASPOT 8, an orange fleshed variety biofortified with provitamin A, and NAROSPOT 1 (white fleshed) have potential productivity of 33 and 35 MT/ha, respectively (Mwanga et al, 2009) but with reported actual yields of 4.4 t/ha at the national level (Loebenstein et al, 2003;Magunda, 2020). Furthermore, these varieties are not widely grown by farmers (Barker et al, 2009;McEwan et al, 2022). Past studies have sought to address farmers' low uptake of improved varieties.…”
Section: Introductionmentioning
confidence: 99%